Associations Between Sexual Violence and Women’s Sexual Attitudes, Sexual Self-Consciousness, and Sexual Self-Efficacy - Alan Dikmen, Hacer (Journal of interpersonal violence, 2021)
Sexual violence, a public health problem, can be seen in all societies and among individuals from all levels of educational background. It is important to be aware of the social and individual factors associated with sexual violence to prevent and fight sexual violence. In this study, it was aimed to determine the associations between sexual violence and women’s sexual attitudes, sexual self-consciousness, and sexual self-efficacy. This is a descriptive study. The data were collected from 469 women admitted to three family health centers in Turkey between May and September 2018. Data were collected using a data collection form and three scales (the Sexual Self-Consciousness Scale, the Sexual Self-efficacy Scale, and the Hendrick Brief Sexual Attitudes Scale). The data were analyzed using descriptive statistics as well as the independent-sample t test and logistic regression analysis. It was found that 37.7% of the women were exposed to sexual violence. The most frequent response of the women against sexual violence was “crying” with 61%. The first reason why the women maintained the marriage despite sexual violence was to avoid their children growing up without a father (43.3%). There was a statistically significant difference between sexual violence and sexual embarrassment, sexual self-focus, sexual self-consciousness, and sexual self-efficacy scores of the women (p < .001). No significant difference between the means of the women’s sexual attitude scores and their sexual violence experiences was observed (p = .526). There was an association between sexual violence and sexual self-efficacy (p = .036; odds ratio [OR] = 1.030, 95% confidence interval [CI] = [1.002, 1.059]). Health professionals may provide sexuality education programs at family health centers, especially for couples preparing for marriage to increase sexual efficacy. Moreover, education may be provided identifying sexual violence acts in marriage and informative awareness programs may be offered regarding sexual violence.